2016
DOI: 10.2147/dddt.s106412
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of cisplatin resistance in cervical cancer

Abstract: Patients with advanced or recurrent cervical cancer have poor prognosis, and their 1-year survival is only 10%–20%. Chemotherapy is considered as the standard treatment for patients with advanced or recurrent cervical cancer, and cisplatin appears to treat the disease effectively. However, resistance to cisplatin may develop, thus substantially compromising the efficacy of cisplatin to treat advanced or recurrent cervical cancer. In this article, we systematically review the recent literature and summarize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
217
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(237 citation statements)
references
References 94 publications
2
217
0
5
Order By: Relevance
“…Platinum‐based chemotherapy is the standard treatment for patients with advanced or recurrent cervical cancer who cannot be operated and irradiated (Leath & Straughn, 2013). However, cisplatin also has adverse side effects in patients with cancer, and the development of drug resistance limits its therapeutic effects (Shen, Pouliot, Hall, & Gottesman, 2012; Zhu et al, 2016). Cervical cancer patients with chemotherapy‐resistant and recurrent cancers usually have a very poor prognosis and low 5‐year survival rate (Li, Hu, Wang, & Yang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Platinum‐based chemotherapy is the standard treatment for patients with advanced or recurrent cervical cancer who cannot be operated and irradiated (Leath & Straughn, 2013). However, cisplatin also has adverse side effects in patients with cancer, and the development of drug resistance limits its therapeutic effects (Shen, Pouliot, Hall, & Gottesman, 2012; Zhu et al, 2016). Cervical cancer patients with chemotherapy‐resistant and recurrent cancers usually have a very poor prognosis and low 5‐year survival rate (Li, Hu, Wang, & Yang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Ratih Dewi Yudhani 1 *, Indwiani Astuti 2 , Mustofa Mustofa 2 , Dono Indarto 3 , Muthmainah Muthmainah 4 cells, E6 HPV protein enhances degradation of p53 protein through binding with leucine rich motifs of E6-associated protein in the ubiquitin ligase (Scheffner et al, 1993;Saha et al, 2012;Ajay et al, 2012;Martinez-Zapien et al, 2016). These protein binding complexes contribute in cisplatin resistance of some cancer cells including cervical cancer (Florea and Büsselberg, 2011;Yang-Hartwich et al, 2014;Zhu et al, 2016). Thus, restoration of p53 function is crucial in the management of HPV-associated cervical cancer because HeLa cells were treated with celecoxib (non-steroidal anti-inflammatory drug) could re-activate p53 via induction of ataxia telangiectasia mutated-/p38 mitogen-activated protein kinase and down regulation of cycloxygenase-2 (Saha et al, 2012).…”
Section: Metformin Modulates Cyclin D1 and P53 Expression To Inhibit mentioning
confidence: 99%
“…However, the development of chemoresistance is commonly seen, which could lead to poor survival. 9 Caspase-3 is a caspase protein that plays pivotal roles in cancer biology mainly by regulating cancer cell apoptosis. 10 It has been reported that the inhibition of caspase-3 is closely correlated with the development of drug resistance in cancer cells during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%